midpoint= (1, 1)
Xm = 1 Ym = 1
G( -4, 6)
This implies that;
x₂= -4 y₂ = 6
Let the coordinates of F by (x₁ y₁)
![x_m=(x_1+x_2)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/2fy4avxlv7higoh77eokm6ns0husy3yse5.png)
Xm = 1 x₂= -4
substitute in the above and then solve for x₁
That is;
![1=(x_1-4)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/thjhi69lvq6j4m2k76qhqn7z4a6apzikp6.png)
2 = x₁ - 4
add 4 to both-side of the equation
6 = x₁
x₁=6
Similarly;
![y_m=(y_1+y_2)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/w6h9ya373ss64g2dwlgurzo33gwlvt2fen.png)
Ym= 1 y₂= 6
substitute the value in the above and solve for y₁
That is;
![1=(y_1+6)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/2q45qw70t5r6zj2n5mq29xbjo5ei93934s.png)
2= y₁ + 6
subtract 6 from both-side of the equation
2-6 =y₁
-4 = y₁
y₁= -4
The coordinates of F are ( 6, -4)